Economic Empowerment of Female-Headed Households Through Baznas Productive Zakat Program In North Lombok Regency - Mahfuz, Muhammad; Anam, Ahmad Gautsul; Putri, Suci Ramadhani (Business Management, 2026)
This study explores the implementation of productive zakat programs by the National Amil Zakat Agency (BAZNAS) in empowering the economy of female-headed households in North Lombok Regency. Female-headed households face significant economic challenges due to limited access to capital, markets, and technology. The BAZNAS productive zakat program aims to provide sustainable economic empowerment through the distribution of MSME carts to 261 beneficiaries. This qualitative research employs a case study approach with data collection techniques including in-depth interviews and participatory observation. Research informants include female-headed household beneficiaries, BAZNAS program managers, facilitators, community leaders, as well as family members and neighbors. Data analysis was conducted using a thematic approach. Research findings indicate that the productive zakat program makes a positive contribution to increasing income and economic independence of female-headed households. However, several constraints were identified in program implementation, including limited continuous mentoring and restricted market access. BPS 2024 data shows that 10.75% of households in North Lombok are headed by women, with a female labor force participation rate of 69.91%. This study recommends program optimization through strengthening mentoring, expanding marketing networks, and developing specific programs responsive to the needs of female-headed households.